1998
DOI: 10.1104/pp.117.4.1325
|View full text |Cite
|
Sign up to set email alerts
|

Expressed Sequence Tags from a Root-Hair-Enriched Medicago truncatula cDNA Library1

Abstract: The root hair is a specialized cell type involved in water and nutrient uptake in plants. In legumes the root hair is also the primary site of recognition and infection by symbiotic nitrogenfixing Rhizobium bacteria. We have studied the root hairs of Medicago truncatula, which is emerging as an increasingly important model legume for studies of symbiotic nodulation. However, only 27 genes from M. truncatula were represented in GenBank/EMBL as of October, 1997. We report here the construction of a root-hairenri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(57 citation statements)
references
References 42 publications
2
55
0
Order By: Relevance
“…RNA samples were separated on a 12 g L Ϫ1 agarose gel containing 62 mL L Ϫ1 formaldehyde. The RNA was transferred to a nylon membrane (Hybond N, Amersham Biosciences UK, Ltd, Little Chalfont, Buckinghamshire, UK) and hybridized with a 280-bp fragment from exon 2 of RIP1 (Cook, Dreyer et al, 1995) and secondarily with a 720-bp fragment that represents a full-length cDNA clone of an actin homolog identified from the M. truncatula expressed sequence tag database (Covitz et al, 1998).…”
Section: Rna Gel-blot Analysismentioning
confidence: 99%
“…RNA samples were separated on a 12 g L Ϫ1 agarose gel containing 62 mL L Ϫ1 formaldehyde. The RNA was transferred to a nylon membrane (Hybond N, Amersham Biosciences UK, Ltd, Little Chalfont, Buckinghamshire, UK) and hybridized with a 280-bp fragment from exon 2 of RIP1 (Cook, Dreyer et al, 1995) and secondarily with a 720-bp fragment that represents a full-length cDNA clone of an actin homolog identified from the M. truncatula expressed sequence tag database (Covitz et al, 1998).…”
Section: Rna Gel-blot Analysismentioning
confidence: 99%
“…The concept of using cDNAs as a route to expedite gene discovery was first demonstrated in the early 1980s (Putney et al 1983). Later gene discovery in most plants was done primarily by sample sequencing of expressed sequence tags (ESTs) (Lim et al 1996;Covitz et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, both functional and structural genomics approaches are being pursued within each of these species. Covitz et al (1998) reported the sequencing of about 900 cDNA tags from the M. truncatula root hairs. In addition, hundreds more expressed sequence tags (ESTs) have been isolated and characterized from effective root nodules of L. japonicus and M. truncatula, and a number of genes showing enhanced expression in plant-rhizobium symbiosis were identified Gyö rgyey et al, 2000).…”
mentioning
confidence: 99%